Motor overflow in Huntington's disease. Issue 6 (14th May 2004) - Georgiou-Karistianis, N; Hoy, K E; Bradshaw, J L; Farrow, M; Chiu, E; Churchyard, A; Fitzgerald, P B; Armatas, C A
Abstract : We investigated both motor overflow and ability to control voluntary movement in patients with Huntington's disease (HD). We hypothesised that, compared with controls, overflow would be significantly greater in HD participants and that they would exhibit poorer control of voluntary movement. In a finger flexion task, participants had to maintain target forces representing 25, 50, or 75% of the maximum strength capacity for whichever finger was performing the task; overflow was measured in the corresponding finger of the non-responding hand. HD participants exhibited significantly greater motor overflow than controls, and more difficulty controlling the target force with the active hand. In addition, the degree of overflow in HD participants positively correlated with overall UHDRS motor symptom severity.The presence of exacerbated motor overflow in HD, and its correlation with symptom severity, is an important finding worthy of further investigation.